Tak en de oppositie tegen de Kieswet. . V.l.n.r.: Van Tienhoven, Van Houten (met schop), Schaepman, ?, Mackay en Tak - Braakensiek, Johan
Tak en de oppositie tegen de Kieswet. V.l.n.r.: Van Tienhoven, Van Houten (met schop), Schaepman, ?, Mackay en Tak.